The inﬂuence of hydrostatic pressure on phase transition in ferroelectrics of displacement type - Slivka, A.G. (Condensed Matter Physics, 2000)
Within the phenomenological theory of phase transitions the temperature change in electrostriction coefﬁcients has been shown to lead to Curie- Weiss constant pressure dependence, non-linearity of phase p, T -diagram and change in phase transition character in ferroelectrics of displacement type.